2016
DOI: 10.1371/journal.pone.0164769
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleepwalking: A Systematic Review and Meta-Analysis

Abstract: Sleepwalking is thought to be a common arousal disorder; however, the epidemiology of this disorder has not yet been systematically examined. A systematic search of MEDLINE, CINAHL, EMBASE, PsycINFO, PubMed, and ScienceDirect was conducted for ‘sleepwalking’ OR ‘somnambulism’ in any field, to identify studies that reported the epidemiology of sleepwalking or sleepwalking disorders. Fifty-one studies assessed the prevalence rates of sleepwalking in a total sample of 100 490. The meta-analysis showed the estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(42 citation statements)
references
References 68 publications
0
40
2
Order By: Relevance
“…Recent meta-analysis suggested relatively few people start sleepwalking in adulthood from the finding that the lifetime prevalence of SW does not significantly vary between childhood and adulthood. 4 The mechanism is not clear why preschool children have more common NREM parasomnia than adults. There is a theoretical assumption that synaptic pruning during childhood to remove redundant excessive synapses including GA-BAergic descending inhibition might contribute to activation 7 Obstructive sleep apnea is known as a risk factor of NREM parasomnia in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analysis suggested relatively few people start sleepwalking in adulthood from the finding that the lifetime prevalence of SW does not significantly vary between childhood and adulthood. 4 The mechanism is not clear why preschool children have more common NREM parasomnia than adults. There is a theoretical assumption that synaptic pruning during childhood to remove redundant excessive synapses including GA-BAergic descending inhibition might contribute to activation 7 Obstructive sleep apnea is known as a risk factor of NREM parasomnia in both children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prevalence of adult SW is 2-4%. 3,4 NREM parasomnia in adult could occur with triggers including combined sleep disorders, alcohol abuse or medication. 3,4 We report a 25-year-old male patient with severe obstructive sleep apnea (OSA) and a history of spontaneous remission of SW in childhood, who developed recurrent SW and dangerous complex motor behaviors during sleep after severe sleep deprivation.…”
mentioning
confidence: 99%
“…Type of Article N Method of Data Collection [7] Longitudinal study N = 9142 Parent-reported behavior [8] Population based cross-sectional study N = 1000 Telephone interview [9] Systematic review and meta-analysis following PRISMA guidelines 51 studies included, N = 100490 Varied [11] Longitudinal study N = 1353 Parent-reported behavior [10] Cross-sectional study N = 700 Self-report questionnaire [12] Review of online surveys Overall N not reported Varied [13] Cross-sectional study N = 19961 Telephone interview…”
Section: Referencementioning
confidence: 99%
“…1 The prevalence of sleep disturbances in children fall within a wide range, between 6 to 43%, depending on the parameters used to determine sleep disorders in some studies. [2][3][4][5] However, complaints can be higher according to the National Sleep Foundation Poll, since 69% of parents reported that their children showed some sleep problems in the course of the week previous to the interview. 6 Common sleep disturbances in children include the difficulty to initiate and maintain sleep, present between the 10 and 40%, 7,8 daytime sleepiness, which has been reported to occur between 10 and 65%.…”
Section: Introductionmentioning
confidence: 99%